Servant Leadership and Innovative Work Behavior: The Mediating Role of Job Crafting and Job Autonomy - Zein, Soeltan Mahzar; Hasibuan, Jasman Saripuddin; Jufrizen, Jufrizen (International Journal of Business Economics (IJBE), 2024)
Purpose – This study examines how job crafting and job autonomy at the Sub Pelindo Multi Terminal Belawan Branch Office, directly and indirectly, affect workers’ creative work behavior under servant leadership.Methodology – The research methodology utilized in this study is a quantitative associative approach. The study included 98 Sub Pelindo Multi Terminal Belawan Branch personnel in its demographic and sample. Data gathering was performed by employing questionnaires and interviews. Data in the current study was gathered by administering a Likert scale questionnaire. The gathered data was subsequently analyzed using SmartPLS 4.0 software in combination with SEM-PLS (Structural Equation Modelling - Partial Least Squares).Findings – The impact of servant leadership on innovative work behavior, job crafting, and job autonomy was positive and statistically significant. Furthermore, the presence of autonomy and job crafting has a significant impact on innovative work behavior. Job autonomy and job crafting mediate the association between servant leadership and creative work behavior.Originality/Novelty – Combining two main concepts as mediating variables, namely job crafting and job autonomy, in one research model to provide a deeper understanding of the complexity of the relationship between the variables of servant leadership, job crafting, job autonomy, and innovative work behavior.Implications – This study suggests that the connection between servant leadership and innovative work behavior is influenced by the involvement of task crafting and autonomy as mediators. Future studies should include investigating or using the variables of job crafting and job autonomy as independent factors rather than as mediatory variables